The Clinical Course after Long‐Term Acute Care Hospital Admission among Older Medicare Beneficiaries. Issue 11 (26th August 2019) - Makam, Anil N.; Tran, Thu; Miller, Michael E.; Xuan, Lei; Nguyen, Oanh Kieu; Halm, Ethan A.
Abstract : Objectives: Long‐term acute care (LTAC) hospitals provide extended complex post–acute care to more than 120 000 Medicare beneficiaries annually, with the goal of helping patients to regain independence and recover. Because little is known about patients' long‐term outcomes, we sought to examine the clinical course after LTAC admission. Design: Nationally representative 5‐year cohort study using 5% Medicare data from 2009 to 2013. Setting: LTAC hospitals. Participants: Hospitalized Medicare fee‐for‐service beneficiaries 65 years of age or older who were transferred to an LTAC hospital. Measurements: Mortality, recovery (defined as achieving 60 consecutive days alive without inpatient care), time spent in an inpatient facility following LTAC hospital admission, receipt of an artificial life‐prolonging procedure (feeding tube, tracheostomy, hemodialysis), and palliative care physician consultation. Results: Of 14 072 hospitalized older adults transferred to an LTAC hospital, median survival was 8.3 months, and 1‐ and 5‐year survival rates were 45% and 18%, respectively. Following LTAC admission, 53% never achieved a 60‐day recovery. The median time of their remaining life a patient spent as an inpatient after LTAC admission was 65.6% (interquartile range = 21.4%‐100%). More than one‐third (36.9%) died in an inpatient setting, never returning home after the LTAC admission. During the preceding hospitalization and index LTAC admission, 30.9% received an artificial life‐prolonging procedure, and 1% had a palliative care physician consultation. Conclusion: Hospitalized older adults transferred to LTAC hospitals have poor survival, spend most of their remaining life as an inpatient, and frequently undergo life‐prolonging procedures. This prognostic understanding is essential to inform goals of care discussions and prioritize healthcare needs for hospitalized older adults admitted to LTAC hospitals. Given the exceedingly low rates of palliative care consultations, future research is needed to examine unmet palliative care needs in this population. J Am Geriatr Soc 67:2282–2288, 2019